Description of Careless English Mistakes (CEMIs) made by EFL students at Gimnasio Colombo Británico in Bogotá, Colombia (2017)
A phenomenon too familiar in English language learning, mistakes are deemed necessary in the process of second language acquisition, SLA and second language learning, SLL and not a mere indication of a student’s learning deficiency. While language learning cannot be achieved without making mistakes, the repetition of the same type of ‘avoidable’ mistakes delays learning. As evidenced from written texts, these mistakes are prevalent among teenagers in a bilingual school in Colombia where most eighth graders, when prompted, can correct the mistakes themselves. One of the causes for these mistakes can be found in one of the various dimensions of Crosslinguistic Influence (Jarvis & Pavlenko, 2008), where the production of the target language (TL) is sometimes ‘influenced’ by the speaker’s mother tongue, MT; the outcome of which is referred to as Interlanguage (IL) Selinker (1972, 1992). This study will delve into the nature of these most common non-developmental mistakes made through IL and explain how they have become fossilised (Selinker, 1972). These mistakes have been collected and systematically complied into a corpus, and are referred to in this study as Careless English Mistakes (CEMIs). The objectives of this study are to investigate the reasons why students make CEMIs, categorise the mistakes, and provide certain strategies to improve students’ accuracy. Contact e-mail: Ldewaal@gmail.com Leonardo de Waal